Factor influencing credit card spending behavior among residents at Bandar Laguna Merbok / Nurul Syuhada Soliano and Ainnur Wahida Ahmad Saad - Soliano, Nurul Syuhada; Ahmad Saad, Ainnur Wahida (2014)
Credit card are a popular medium of payment for consumer today that has been identified as the second most popular non-cash instrument (Chakravorti, 2003). The use of credit cards has already become a convenient way to expand purchasing power (Braunsberger, 2004). Other than that, in modem commerce, credit cards serve as a payment device in lieu of cash or checks for millions of routine purchases as well as for many transactions that would otherwise be inconvenient or perhaps impossible (Durkin, 2000). It is clearly specify that the spending behaviour of credit card holders will be affected by the factor influencing credit card spending behaviour. It shows, the use of credit card will relates to customer attitude. This study consider Malaysia as its setting in view of the interesting developments that have since take place as compare to other countries in term of legal, structural, cultural, geographical, and socio-economic differences between countries.